Grid integration policies of gas-fired cogeneration in Peninsular Malaysia: fallacies and counterexamples - Shaaban, Mohamed (Elsevier Ltd, 2011)
Despite the abundance of natural gas reserves in Malaysia coupled with serious government thrusts to promote cogeneration, its (cogeneration) development pace lags far off expectations. There are widespread fallacies among potential cogeneration developers and concerned professionals that cogeneration is uncompetitive in Malaysia due to existing policies of subsidized gas prices and grid-connection charges. This paper exposes these fallacies through counterexamples of practical cogeneration system design and evaluation of some segments of the industrial and service sectors in Peninsular Malaysia. The electrical and thermal characteristics of the cogeneration were modeled based on heat rate characteristics at partial loading patterns. A hierarchical mathematical programming approach that uses mixed-integer nonlinear optimization and dynamic programming principle, if necessary, is employed to determine the optimal size of cogeneration and its related auxiliary equipment as well as the optimal operation schedule. Financial assessment is integrated at a later stage to assess the economic viability of the system. Analyses of the cogeneration potential for several facilities of miscellaneous activities were carried out using various gas and electricity prices. Results obtained consistently rebuff the perpetuated fallacies and confirm that there is no real barrier to cogeneration development in Malaysia under current policies of gas prices and electricity tariffs.